Sistem Informasi Rekam Medis Elektronik (RME) Puskesmas di Lingkungan Dinas Kesehatan, Pengendalian Penduduk dan Keluarga Berencana Kabupaten Batu Bara - Dedek Haryati Damanik (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
The Electronic Medical Record Information System (RME) is an information technology solution used to manage patient medical record data digitally, replacing manual recording systems that are prone to errors and data loss. This report discusses the design and implementation of the Electronic Medical Record Information System (RME) at the Community Health Center, which aims to increase efficiency, accuracy and security in managing patient medical records. This system includes recording medical data, treatment history, diagnosis, drug prescriptions, as well as integration with other health service systems. With RME, the medical service process at the Community Health Center is expected to be faster, more transparent and organized. This research uses a web-based system development method with database-based programming, which allows medical record data to be managed centrally and easily accessed by authorized medical personnel. The results of implementing this system show a significant increase in speed of service as well as a reduction in administrative and medical errors.